Validating Workplace Safety Scale (WSS) and its influence on workplace safety sustainability in the health care sector - Subramaniam, Chandrakantan; Mohd Shamsudin, Faridahwati; Mohd Zin, Md. Lazim; Ibrahim, Hadziroh; Mad Lazim, Halim; Abd Aziz, Fadzli Shah (Universiti Utara Malaysia, 2014)
The present study attempts to provide empirical evidence on the relationship between the five facets of workplace safety scale and safety compliance behaviour.In adfdition the study examined the interaction effects of age on these workplace safety and safety compliance behaviour.The dimensions considered in the study are job safety, co-worker safety, supervisory safety, management safety, and satisfaction with safety programs/policies.Toward this end, a survey among 351 nurses working in Hospital Tuanku Fauziah Kangar, Hospital Sultanah Bahiyah Alor Setar, Penang General Hospital and Hospital Taiping was carried out.Self- reported measures were used to obtain data pertaining to workplace safety dimensions and safety compliance behaviour. The Partial Least Square (PLS) structural model analysis was used to ascertain the proposed relationships and it was found that only three dimensions of workplace safety (co- worker safety, supervisor safety and satisfaction with safety programs) were significantly related to safety compliance behaviour. Meanwhile, the results indicate that the moderating interaction of age on the relationship between job safety, co-worker safety, supervisor safety, management safety, and satisfaction on safety compliance behaviour were not significant.Discussion on the findings is highlighted, so as the implications for practice and future research. Limitations of the study are also offered.